Enhanced autophagy in pulmonary endothelial cells on exposure to HIV-Tat and morphine: Role in HIV-related pulmonary arterial hypertension. Issue 12 (1st December 2016) - Dalvi, Pranjali; Sharma, Himanshu; Chinnappan, Mahendran; Sanderson, Miles; Allen, Julie; Zeng, Ruoxi; Choi, Augustine; O'Brien-Ladner, Amy; Dhillon, Navneet K.
ABSTRACT: Intravenous drug use is one of the major risk factors for HIV-infection in HIV-related pulmonary arterial hypertension patients. We previously demonstrated exaggerated pulmonary vascular remodeling with enhanced apoptosis followed by increased proliferation of pulmonary endothelial cells on simultaneous exposure to both opioids and HIV protein(s). Here we hypothesize that the exacerbation of autophagy may be involved in the switching of endothelial cells from an early apoptotic state to later hyper-proliferative state. Treatment of human pulmonary microvascular endothelial cells (HPMECs) with both the HIV-protein Tat and morphine resulted in an oxidative stress-dependent increase in the expression of various markers of autophagy and formation of autophagosomes when compared to either Tat or morphine monotreatments as demonstrated by western blot, transmission electron microscopy and immunofluorescence. Autophagy flux experiments suggested increased formation rather than decreased clearance of autolysosomes. Inhibition of autophagy resulted in a significant increase in apoptosis and reduction in proliferation of HPMECs with combined morphine and Tat (M+T) treatment compared to monotreatments whereas stimulation of autophagy resulted in opposite effects. Significant increases in the expression of autophagy markers as well as the number of autophagosomes and autolysosomes was observed in the lungs of SIV-infected macaques and HIV-infected humans exposed to opioids. Overall our findings indicate that morphine in combination with viral protein(s) results in the induction of autophagy in pulmonary endothelial cells that may lead to an increase in severity of angio-proliferative remodeling of the pulmonary vasculature on simian and human immunodeficiency virus infection in the presence of opioids.